Antiosteoporosis Studies of 20 Medicine Food Homology Plants Containing Quercetin, Rutin, and Kaempferol: TCM Characteristics, In Vivo and In Vitro Activities, Potential Mechanisms, and Food Functions. (31st March 2022) - Shen, Dayue; Feng, Yating; Zhang, Xilan; Gong, Le; Liu, Jing; Li, Yuanping; Liao, Hui
Abstract : Dietary nutraceutical compounds have been evidenced as backbone for bone health in recent years. It is reported that medicine food homology (MFH) plants have multiple nutraceutical compounds. Based on our literature research, 20 MFH plants caught our attention because they contain three popular antiosteoporosis compounds simultaneously: quercetin, rutin, and kaempferol. According to traditional Chinese medicine (TCM), their characteristics including natures, flavors, attributive to meridian tropism, and efficacies were listed. The relationships between TCM efficacies, such as "heat clearing, " "tonic, " and "the interior warming, " and antiosteoporosis pharmacological actions such as antioxidant and immune regulation were discussed. The in vivo antiosteoporosis effects of the 20 MFH plants were summarized. The in vitro antiosteoporosis activities and related mechanisms of the 20 plants and quercetin, rutin, kaempferol were detailed. The TGF- β -Smad signaling, fibroblast growth factor, and Wnt/ β -catenin signaling on bone formation and the RANKL signaling, NF- κ B signaling, and macrophage-colony-stimulating factor on bone resorption were identified. From food point, these 20 MFH plants could be classified as condiment, vegetable, fruit, tea and related products, beverage, etc. Based on the above discussion, these 20 MFH plants could be used as daily food supplements for the prevention and treatment against osteoporosis.